2021
DOI: 10.1016/j.jbo.2021.100376
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis or osteosynthesis for the treatment of a pathological hip fracture? A nationwide registry-based cohort study

Abstract: Highlights Prostheses result in lower pain than osteosyntheses in pathological hip fractures. Surgeons in sarcoma centers generally use prostheses for pathological hip fractures. Both methods use similar healthcare resources and effectively restore ambulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Pathologic fractures especially those exposed to radiation rarely, if ever, heal 53 . A nationwide Swedish study of 980 patients found an endoprosthetic to be superior in function and pain relief compared with osteosynthesis for pathologic fractures of the proximal femur 54 . In patients with more disseminated disease, surgeons should take care to augment their construct with long-stemmed options versus a long lateral plate to bridge the diseased bone.…”
Section: Treatmentmentioning
confidence: 99%
“…Pathologic fractures especially those exposed to radiation rarely, if ever, heal 53 . A nationwide Swedish study of 980 patients found an endoprosthetic to be superior in function and pain relief compared with osteosynthesis for pathologic fractures of the proximal femur 54 . In patients with more disseminated disease, surgeons should take care to augment their construct with long-stemmed options versus a long lateral plate to bridge the diseased bone.…”
Section: Treatmentmentioning
confidence: 99%
“…One of the methods used in the treatment of hip fractures is endoprosthesis. [5][6][7][8] In this method, the operation involves fitting a fracture prosthesis. Endoprosthesis, which provides more advantages compared to those of traditional hip fracture methods, may be applied as in part or its entirety.…”
Section: Introductionmentioning
confidence: 99%
“…Among these surgical procedures, the hip joint becomes a challenging point for treatment due to its unique anatomical position [12], especially involving lesions in the hip socket and pelvic stress conduction area. These joints bear enormous stress when standing under load, making them the most common site for pathological fractures [13]. Periarticular metastatic damage often causes gradual displacement of the femoral head towards the top and inner side of the acetabulum, sometimes resulting in acute acetabular fractures or collapse; despite effective radiotherapy, this site may experience local bone dissolution and necrosis, leading to pathological fractures or joint collapse [14].…”
Section: Introductionmentioning
confidence: 99%